Confessional space and its structure in the context of human geography research - Ivan Kostaschuk; Roman Kisil (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
On the basis of analysis of the works of many scientists, we concluded that the confessional space is different from the concepts of confession, religious sphere and religious space. They all have different scientific explanation and interpretation, although sometimes they have been used as synonyms in Ukrainian social geography. Confessional space differs from religious space, primarily in the fact, that it does not include atheists, agnostics and others, who do not associate themselves with any beliefs.